Kinerja Penyuluh Agama Islam Fungsional Dalam Pembinaan Umat di Kota Padang - ZAINUL WAHAB (STAI Hubbulwathan Duri, 2018)
Islamic extension workers are very important and strategic, besides carrying out guidance and counseling, they also provide information and motivation to the implementation of development programs to the community. This shows that the Islamic Religion Instructor as a guide to the community in the field of religion also plays a role as a community leader. This role is the main task for a religious instructor in order to uphold the amar ma'ruf nahi munkar which aims to increase the faith and piety of the people to Allah SWT so that they become people who are religious, virtuous and have social attitudes towards others. As leaders or community leaders, religious educators will become the foundation for the community in solving various life problems, even they are expected to be able to provide changes, as well as motivators, dynamists and mobilizers in physical and mental development. Islamic extension workers as the spearhead of the implementation of guidance or counseling for the community in the religious field, have a strategic role in realizing education in the community through the language of religion.